Releasable AlGaN/GaN 2D electron gas heterostructure membranes for flexible wide-bandgap electronics - Zhang, Yi-Yu (2022)
The development of transferrable free-standing semiconductor materials and their heterogeneous integration to arbitrary substrates open up new possibilities in improving device performance, exploring nonconventional manufacturing approaches, and offering a pathway to soft, conformal, and flexible electronics. In this work, flexible AlGaN/GaN high-electron mobility transistors (HEMTs) are demonstrated, which are transfer-printed from AlGaN/GaN on insulator to a flexible substrate using a novel releasing strategy based on the fast, facile, and reliable transfer process. Flexible AlGaN/GaN HEMTs possess good electrical performance such as the maximum saturated drain current density and transconductance of 110 mA mm−1 and 42.5 mS mm−1, respectively. Moreover, a significant piezoelectric behavior is observed when the device is under strain, resulting from the piezoelectric-induced polarization at the heterostructure interface. Owing to an additional strain-induced piezoelectric effect by the mechanical bending, the performance of AlGaN/GaN HEMT can be further improved. The results demonstrate that the device has great potential in applications for the next-generation flexible electronics, such as wearable systems, intelligent microinductor systems, and smart systems that can sense or feedback external mechanical stimuli.